2013
DOI: 10.1080/00220388.2012.740014
|View full text |Cite
|
Sign up to set email alerts
|

Look Who's Talking: The Impacts of the Intrahousehold Allocation of Mobile Phones on Agricultural Prices

Abstract: Using data from the Philippines, we study the impact of mobile phones on the prices agricultural producers receive for their cash crop. We first look at the impact on price of mobile phone ownership at the household level. Because this masks a considerable amount of heterogeneity, we then look at the impact on price of the intrahousehold allocation of mobile phones. We find that whether the household owns a mobile phone has no impact on price, but whether a farmer or his spouse own a mobile phone is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Aparjita [23] proposed that the use of information technology could help farmers obtain transparent price information and reduce production costs. Jensen [24] and Lee [25] suggested that the application of information technology could significantly increase the price of farmers' products and income [26,27]. Some scholars have also proposed that information technology can improve production efficiency and reduce labor costs [28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aparjita [23] proposed that the use of information technology could help farmers obtain transparent price information and reduce production costs. Jensen [24] and Lee [25] suggested that the application of information technology could significantly increase the price of farmers' products and income [26,27]. Some scholars have also proposed that information technology can improve production efficiency and reduce labor costs [28][29][30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such scholars showed that mobile phones resulted in reduced price dispersion across markets (e.g. Aker, 2008;Tack & Aker, 2014) and increased crop prices, presumably due to increased bargaining power (Lee & Bellemare, 2013;Zanello, Srinivasan & Shankar, 2014). Some authors found that the mobile phone led to increased market participation by farmers, but only for perishable crops (Muto & Yamano, 2009;Egyir et al, 2011).…”
mentioning
confidence: 99%
“…Remarkably, mobile phones do not influence farmers' bargaining position, contrarily to quantitative research such as Lee and Bellemare (2013) and Zanello et al (2014). Those authors studied correlations between mobile phones and crop-prices and market participation respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The study, conducted in Ghana, revealed that farmers directly connected with the buyers through cell phones receive better prices for their agricultural goods as compared to using the brokers. Farmers with the cell phones can eliminate transport cost (Overa, 2006) while saving money, time and energy by avoiding going to the markets (Muto & Yamano 2009;Muto & Yamano., 2011;Lee & Bellemare, 2013). Cell phone-enabled technologies are also used to monitor and disseminate information about the out breaking of crop diseases (Ndyetabula & Legg, 2011;Kefala, 2011).…”
Section: Introductionmentioning
confidence: 99%